Lexical diversity in early learning of English as L2 - Mihaljević-Djigunović, Jelena; Letica Krevelj, Stela (2011)
In this paper the authors discuss L2 lexical diversity in the context of early learning of English as L2. They describe the study they carried out with Croatian early beginners in order to see which levels of lexical diversity they reached after four years of learning and which linguistic and non-linguistic factors lexical diversity interacted with. Their findings indicate that young learners differ in their lexical development and that lexical diversity interacts with the learners' attitudes, motivation and self- concept as well as a number of contextual factors.
Projekt MZOS
ENG